Determinate factors of mental health status in Chinese medical staff: A cross-sectional study. Issue 10 (March 2018) - Zhou, Chenyu; Shi, Lei; Gao, Lei; Liu, Wenhui; Chen, Zhenkang; Tong, Xinfa; Xu, Wen; Peng, Boshi; Zhao, Yan; Fan, Lihua
Abstract : Abstract: Numerous previous studies have investigated the mental health status of medical staff in China and explored its associated determinate factors; however, scope and methods associated with these have introduced uncertainty regarding the results. The aim of this study was to perform a comprehensive examination of the mental health status of Chinese medical staff and its relative risk factors based on a cross-sectional survey. We conducted a broad area, cross-sectional, questionnaire-based survey of Chinese medical workers. Participants were randomly selected from 27 hospitals in the Heilongjiang province. The questionnaire that was distributed consisted of 5 parts: the demographic characteristics of the participant; questions related to the relative risk factors of psychological health; the posttraumatic stress disorder (PTSD) Checklist-Civilian Version (PCL-C); the Self-rating Depression Scale (SDS); and the Self-rating Anxiety Scale (SAS). The last 3 components were used to evaluate the mental health status of the target population. Logistic and linear regression were used to analyze the determinate factors of the mental health status of Chinese medical staff. Of the 1679 questionnaires distributed, 1557 medical workers responded (response rate: 92.73%; male: 24.1%; female 75.9%). The results of mental health status self-assessments indicated that 32.3% of participants were considered to have some degree of PTSD (based on the PCL-C). The SDS index was 0.67 and the mean score from SAS was 55.26; a result higher than found in the general population. Multivariate logistic regression analysis revealed that being female, dissatisfaction or average satisfaction with income, and good or very good self-perceived psychological endurance when faced with an emergency were associated with a reduction of PTSD symptoms. A frequency of verbal abuse incidents greater than 4 was associated with an increase in PTSD symptoms. The mental health status of Chinese medical staff is poor. While the determinate factors based on different measurement standards were not completely consistent, the overlapping major risk factors identified that influenced psychological health were the amount of education, the perceived level of respect, and psychological endurance.